Xenotransplantation Methods and Protocols - Costa, Cristina; Máñez, Rafael; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2012)
Despite many technological challenges faced by the xenotransplantation field, many major advances have been made in the last two decades. The field seeks to overcome the limitations and difficulties in organ procurement, which also apply to human cells and tissues, and facilitate the development of new therapies based on cell and engineered-tissue. Xenogeneic cells are simpler than solid organs and seem to pose less hurdles to attain long-term graft survival. In, Xenotransplantation: Methods and Protocols expert researchers study characterizations of xenogeneic interactions at the cellular and molecular levels and describe the use of relevant small-animal and pig-to-primate models. Related ethical and legal considerations are also covered. Written in the highly successful Methods in Molecular Biology™ series format, the chapters include the kind of detailed description and implementation advice that is crucial for getting optimal results in the laboratory.   Thorough and intuitive, Xenotransplantation: Methods and Protocols aids scientists in continuing to study xenotransplantation and its multiple aspects.
Keywords: Cell biology; Cell Biology